2007
DOI: 10.1037/0893-164x.21.2.226
|View full text |Cite
|
Sign up to set email alerts
|

Fake ID ownership and heavy drinking in underage college students: Prospective findings.

Abstract: The authors examined the ownership of false identification (fake ID) for the purpose of obtaining alcohol and the relation of fake ID ownership to heavy drinking in a longitudinal sample of college students under 21 years of age. A sample of 3,720 undergraduates was assessed the summer prior to college entrance and during the 4 semesters comprising freshman and sophomore years. Regression analyses were used to estimate bidirectional relations between consumption and fake ID ownership. Sex, Greek membership, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 19 publications
5
20
0
Order By: Relevance
“…In addition, both socialization and selection can be present at once, and the concept of reciprocal determinism [24] captures the dynamic interplay of selection and socialization processes over time [25]. A good example of such reciprocal influence is demonstrated by the ownership of fake identification (IDs), which are linked to heavy drinking [26]. Before matriculation, future Greek members are more likely to own fake IDs (selection); after matriculation, a greater percentage of Greek members obtain fake IDs than non-members (socialization).…”
Section: Research On Alcohol Use In the Greek Systemmentioning
confidence: 99%
“…In addition, both socialization and selection can be present at once, and the concept of reciprocal determinism [24] captures the dynamic interplay of selection and socialization processes over time [25]. A good example of such reciprocal influence is demonstrated by the ownership of fake identification (IDs), which are linked to heavy drinking [26]. Before matriculation, future Greek members are more likely to own fake IDs (selection); after matriculation, a greater percentage of Greek members obtain fake IDs than non-members (socialization).…”
Section: Research On Alcohol Use In the Greek Systemmentioning
confidence: 99%
“…Technological advances in manufacturing false IDs and the proliferation of web-based sales have contributed to increased false ID use among underage drinkers (Murray, 2005). Few studies have examined the patterns and correlates of false ID use, and many questions remain unanswered regarding how false ID use might influence risk for heavy drinking and/or exacerbate existing alcohol problems Martinez et al (2007). demonstrated that false ID possession among college students increased over time and predicted heavy drinking.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that false ID possession among college students increased over time and predicted heavy drinking. Conversely, heavy drinking predicted subsequent false ID acquisition, even controlling for sex and fraternity/sorority membership (Martinez et al, 2007). A later study by the same group linked frequent heavy drinking with using a false ID to enter a bar and using it to enter multiple venues (Martinez and Sher, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many college student drinkers are under 21 years old, so college drinking is still a problem. It is too easy to obtain a fake ID (Martinez, Rutledge, and Sher 2007). Making it illegal for parents to provide alcohol to those under the legal drinking age (United States)…”
Section: School Education Programs (Various Countries)mentioning
confidence: 99%